High inverted tunneling magnetoresistance in MgO - based magnetic tunnel junctions - FENG, JIA-FENG; COEY, JOHN MICHAEL DAVID (My University, 2007)
Inverted tunneling magnetoresistance, where resistance decreases as the free layer in a magnetic tunnel junction flips its direction of magnetization after saturation, has been observed at zero bias in magnetic tunnel junctions with a thin CoFeB layer in the pinned synthetic antiferromagnetic CoFe/Ru/CoFeB stack. Magnetoresistance values as high as ?55% at room temperature are measured in MgO-based tunnel junctions when the thickness of the pinned CoFeB layer is 1.5 nm. The inverted magnetoresistance is associated with imbalance of the synthetic antiferromagnetic pinned layer. Asymmetric bias dependence with a magnetoresistance sign change is observed for a 0.5 nm pinned CoFeB layer.
PUBLISHED
Keywords: Physics